Transition from Syringe to Autoinjector Based on Bridging Pharmacokinetics and Pharmacodynamics of the P2Y12 Receptor Antagonist Selatogrel in Healthy Subjects - Zenklusen, Isabelle; Hsin, Chih-Hsuan; Schilling, Uta; Kankam, Martin; Krause, Andreas; Ufer, Mike; Dingemanse, Jasper (Clinical pharmacokinetics, 2022)
Background and Objectives Selatogrel is a potent, reversible, and selective antagonist of the platelet P2Y 12 receptor currently developed for the treatment of acute myocardial infarction (AMI). In the completed Phase I/II studies, selatogrel was subcutaneously (s.c.) administered as a lyophilizate-based formulation by syringe by a healthcare professional. In the Phase III study, selatogrel will be self-administered s.c. as a liquid formulation with an autoinjector at the onset of AMI symptoms to shorten treatment delay. This clinical bridging study compared the pharmacokinetics (PK) of selatogrel between the different formulations. Methods This was a single-center, randomized, open-label, three-period, cross-over Phase I study in 24 healthy subjects. In each period, a single subcutaneous dose of 16 mg selatogrel was administered as (1) a Phase III liquid formulation by autoinjector (Treatment A), (2) a Phase III liquid formulation by prefilled syringe (Treatment B), or (3) a Phase I/II reconstituted lyophilizate-based formulation by syringe (Treatment C). PK parameters including area under the plasma concentration–time curve from zero to infinity (AUC 0–∞ ), maximum plasma concentration ( C max ), time to reach C max ( t max ), and terminal half-life ( t 1/2 ) were determined using noncompartmental analysis. Pharmacodynamic (PD) parameters were estimated using PK/PD modeling, including the time of first occurrence of inhibition of platelet aggregation (IPA) ≥ 80% ( t onset ), duration of IPA above 80% ( t duration ), and responder rate defined as the percentage of subjects with t onset ≤ 30 min and t duration ≥ 3 h. Safety and tolerability were also assessed. Results Comparing Treatment A to Treatment C, the exposure (AUC 0–∞ ) was bioequivalent with a geometric mean ratio (GMR) (90% confidence interval) of 0.95 (0.92–0.97) within the bioequivalence range (0.80–1.25). Absorption following Treatment A was slightly slower with a t max occurring approximately 30 min later and a 20% lower C max . The autoinjector itself had no impact on the PK of selatogrel, as similar values of C max and AUC 0–∞ were determined after administration as a Phase III liquid formulation by autoinjector or by prefilled syringe (i.e., GMR [90% confidence interval] of 1.06 [0.97–1.15] and 0.99 [0.96–1.03] for C max and AUC 0–∞ , respectively). PK/PD modeling predicted that the median t onset will occur slightly later for Treatment A (7.2 min) compared to Treatment C (4.2  min), while no relevant differences in t duration and responder rate were estimated between the two treatments. Selatogrel was safe and well tolerated following all three treatments. Conclusions PK and simulated PD effects of selatogrel were similar across treatments. Clinical Trial Registration NCT04557280.